2010
DOI: 10.1103/physrevb.82.195436
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of graphene fluoride and graphane

Abstract: Different stoichiometric configurations of graphane and graphene fluoride are investigated within density functional theory. Their structural and electronic properties are compared, and we indicate the similarities and differences among the various configurations. Large differences between graphane and graphene fluoride are found that are caused by the presence of charges on the fluorine atoms. A new configuration that is more stable than the boat configuration is predicted for graphene fluoride. We also perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
451
4
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(505 citation statements)
references
References 43 publications
45
451
4
5
Order By: Relevance
“…They found that a structure similar to configuration C 12 is lower in formation energy compared to that of C 13 . In this work, we have examined similar configurations on 2×1 single layer graphene, and our results show the same trend as theirs 62 . When 2×1 bilayer graphene is considered, the trend alters.…”
Section: B Stability Analysis and Structural Propertiessupporting
confidence: 58%
See 2 more Smart Citations
“…They found that a structure similar to configuration C 12 is lower in formation energy compared to that of C 13 . In this work, we have examined similar configurations on 2×1 single layer graphene, and our results show the same trend as theirs 62 . When 2×1 bilayer graphene is considered, the trend alters.…”
Section: B Stability Analysis and Structural Propertiessupporting
confidence: 58%
“…This is due to the fact that they are made up of pair combinations of the conformers. The highest formation energy found for C 12 is in contrast with the findings of Leenaerts et al 62 for their studies of a similar kind of hydrogen arrangement on 2×1 single layer graphene. They found that a structure similar to configuration C 12 is lower in formation energy compared to that of C 13 .…”
Section: B Stability Analysis and Structural Propertiescontrasting
confidence: 56%
See 1 more Smart Citation
“…3 (h) where the averaged C-C distance of a hexagon is shown to increase with D H local . This expansion is an additional geometric effect played by sp 3 bonded carbons [47].…”
Section: Figmentioning
confidence: 99%
“…[3][4][5][6] In spite of its unique properties, due to the lack of a band gap and its weak light adsorption, graphene research efforts have focused on graphene composites over the past five years. Studies have demonstrated the existence of several chemically converted graphene structures such as grapheneoxide (GO), 7-9 graphane (CH), [10][11][12][13][14] fluorographene (CF), [15][16][17][18][19] and chlorographene (CCl). [20][21][22] High-quality insulating behavior, thermal stability and extraordinary mechanical strength of fluorographene (CF) has inspired intense research on halogenated graphene derivatives.…”
Section: Introductionmentioning
confidence: 99%